Quercetin ameliorates renal injury in hyperuricemic rats via modulating ER stress pathways - Liu, Huan; Yang, Qi; Wang, Shuiying; Wang, Tingting; Pan, Lihua; Wang, Xue; Chi, Yangfeng; Jin, Zhouhui (Frontiers in Pharmacology, 2025)
Hyperuricemia is a key risk factor for chronic kidney disease (CKD), yet effective treatments remain limited. This study demonstrates that quercetin exerts potent renoprotective effects in hyperuricemia-induced CKD through multifaceted mechanisms. In rats with hyperuricemia induced by adenine (0.1 g/kg) and potassium oxonate (1.5 g/kg), quercetin treatment (50 or 100 mg/kg) significantly improved renal function by reducing urinary ACR, serum creatinine, uric acid, BUN, and blood pressure, while alleviating renal inflammation, fibrosis, and crystal deposition. Mechanistic studies revealed quercetin’s ability to suppress ER stress markers (GRP78, CHOP, p-PERK, IRE1α, ATF6), inhibit renal GLUT9 expression, and downregulate downstream inflammatory (TLR4/NF-κB/IL-1β/TNF-α), fibrotic (collagen I/α-SMA/fibronectin), and oxidative pathways, while enhancing antioxidant defenses and inhibiting apoptosis. Notably, quercetin showed superior efficacy to febuxostat (5 mg/kg), the clinical gold standard. These findings establish quercetin as a promising therapeutic candidate for hyperuricemia-associated kidney injury through its comprehensive modulation of ER stress-mediated pathological processes.